Structures and magnetic properties of Mn and Co inorganic-organic frameworks with mixed linear dicarboxylate ligands - Saines, P; Barton, P; Jain, P; Cheetham, A (2012)
The structures and magnetic properties of two transition metal frameworks that feature a mixture of two linear dicarboxylate ligands are reported. Compounds 1, Mn 2(C 4H 4O 4)(C 6H 8O 4)(H 2O) 4· 2H 2O, and 2, Co 6(C 4H 4O 4) 4(C 6H 8O 4)(OH) 2(H 2O) 4·5H 2O, contain a mixture of succinate and adipate ligands but adopt significantly different structures. Compound 1 features layers of MnO 6 dimers, intra-connected by carboxylate groups, with neighbouring dimers connected to each other via the adipate ligands in one direction and succinate ligands in the other. Extensive hydrogen bonding in the third dimension provides the main force holding layers together. Framework 2 has inorganic layers of CoO 6 octahedra arranged into rings of 14 members each, with adipate ligands providing inter-layer connectivity. The structures of these two compounds are compared to Mn and Co dicarboxylate frameworks containing only one type of organic ligand, including Co(C 6H 8O 4), compound 3, whose structure is reported in this work for the first time; they are found to be significantly different from those that form under similar conditions. Both compounds order magnetically near 2 K. Compound 1 is an antiferromagnet, in which the intra-dimer coupling dominates the magnetic behaviour, while framework 2 is most likely a canted antiferromagnet. Both compounds undergo magnetic phase transitions with increasing applied magnetic fields, at 14 kOe and 0.35 kOe in 1 and 2, respectively. The transition in the Mn compound is a simple spin flop but in the Co compound the suppression of the long range ordered state is also accompanied by the elimination of the ferromagnetic component of its magnetic interactions. © 2012 The Royal Society of Chemistry.